The Provisions of Medical Civil Liability for the Radiology Practitioner - Hadi Kate, Researcher. Noor Al-huda; Abid El Aali Khashan Al Asadi, Prof. Dr. Ali (Basra studies journal, 2024)
The issue of medical civil liability springs from the harms of radiation therapy which is one of the most important and critical issues because of its close association with the physical safety of individuals. Accordingly, the study has researched the nature of compensation and Doctors' commitment. it is a commitment to achieve a result or commitment to achieve a goal, some of them are likely to commit to the result and there are those who think the best commitment is to reach the goal. The researchers have studied the responsibility in terms of its definition, and the statement of types of compensations and their amount by following the method of comparative analytical study between the legislation of three countries, i.e., Iraq, Egypt and France with reference to Jurisprudence opinions and statement of jurisprudence in this regard.